Síntese e avaliação da atividade herbicida de triazóis - Thiago Freitas Borgati (2013)
The use of chemicals (known as herbicides or weed killers) is currently the most cost efficient and reliable weed control method used by farmers. Although there exist several active ingredients available to control weeds, it is necessary to find new herbicides to overcome weed resistance problems provoked by pressure selection. In addition, due to environmental public concerns modern herbicides should have a favorable combination of properties such as high levels of herbicidal activity, low application rates, crop tolerance, and low toxicity to mammals. In the search and development of new herbicides as well as otheragrochemicals and pharmaceuticals, heterocyclic compounds play an important role. The heterocyclic portion of a compound can produce a beneficial effect in terms of its physicochemical properties, conferring lipophilicity, and solubility values that lay in the optimal range for uptake and bioavailability. Halogenated heterocyclic chemicals, for example, are widely used to manufacture pesticides, pharmaceuticals, dyes, and explosives. These compounds are generally polar and consequently, they are often more environmentally mobile. Considering the versatility of the click chemistry as a promising way to make carbon-carbon bonds and the aforementioned biological activity of heterocycles bearing halogen substituents, it is described in this work the synthesis and the phytotoxic activity evaluation of 27 new triazoles having halogens. Among these new compounds, nine were synthesized in six steps while the synthesis of the others 18 were made in three steps. The phytotoxic activity was evaluated under four vegetal species: Cucumis sativus, Lactuca sativa, Bidens pilosa and Allium cepa. All compounds showed great development inhibitory activity under the target species and the best resultswere observed for the compounds having two triazole rings, some of them presented inhibitory activities comparable to 2,4-D, the commercial herbicide used as a reference.